2022
DOI: 10.1161/circulationaha.121.056666
|View full text |Cite
|
Sign up to set email alerts
|

PRDM16 Is a Compact Myocardium-Enriched Transcription Factor Required to Maintain Compact Myocardial Cardiomyocyte Identity in Left Ventricle

Abstract: Background: Left ventricular noncompaction cardiomyopathy (LVNC) was discovered half a century ago as a cardiomyopathy with excessive trabeculation and a thin ventricular wall. In the decades since, numerous studies have demonstrated that LVNC primarily impacts left ventricles (LVs), and is often associated with LV dilation and dysfunction. However, owing in part to the lack of suitable mouse models that faithfully mirror the selective LV vulnerability in patients, mechanisms underlying susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 79 publications
8
85
0
Order By: Relevance
“…For example, overexpression of p16 slowed cell cycle progression in the G0/G1 phase and induced erythroid lineage differentiation [85], which might correspond to the early p16 expression in embryonic mouse livers [86]. Lack of p16 is linked to increased cardiomyocyte proliferation [80], while lower cardiomyocyte proliferation, differentiation, and specification are required for myocardial compaction [87,88], which coincides with our observed cardiac p16 expression.…”
Section: Discussionsupporting
confidence: 83%
“…For example, overexpression of p16 slowed cell cycle progression in the G0/G1 phase and induced erythroid lineage differentiation [85], which might correspond to the early p16 expression in embryonic mouse livers [86]. Lack of p16 is linked to increased cardiomyocyte proliferation [80], while lower cardiomyocyte proliferation, differentiation, and specification are required for myocardial compaction [87,88], which coincides with our observed cardiac p16 expression.…”
Section: Discussionsupporting
confidence: 83%
“…ChIP assays were performed as previously described [ 62 ]. Briefly, the recovered supernatants were incubated with a rabbit anti-Twist1 antibody (#50887, Abcam, Cambridge, United Kingdom) or an isotype control IgG (BD Biosciences, Franklin Lake, NJ, USA) for 2 h in the presence of herring sperm DNA and protein A/G magnetic beads.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms leading to the LVNC phenotype mostly remain unclear, though some authors have pointed to an abnormal cardiac embryogenesis resulting from the intrauterine arrest of normal ventricular myocardium maturation and compaction [ 8 ]. Recent findings from Wu et al [ 9 ] indicated the improper transcriptional specification of compact or trabecular cardiomyocytes as a potential common mechanism in LVNC development.…”
Section: Introductionmentioning
confidence: 99%